Service Quality for Regional Drinking Water Company (PDAM) Sidoarjo Regency: Kualitas Pelayanan Perusahaan Daerah Air Minum (PDAM) Kabupaten Sidoarjo - Rostania, Cici Mei Nur; Mursyidah, Lailul (Indonesian Journal of Public Policy Review, 2021)
Stipulated in the 1945 Constitution, the implementation of public services in Indonesia is an effort to fulfill the basic needs and rights of every citizen. In fact, efforts to provide public services have not run optimally, especially in agencies that provide public services. One of them is the provision of clean water services at the Waru II Branch of Drinking Water Company, Sidoarjo Regency. The purpose of the study was to measure the quality of service at the Regional Drinking Water Company (PDAM) "Delta Tirta" Waru II Branch, Sidoarjo Regency. This research uses descriptive quantitative method. The results of this study indicate that the quality of service affects the performance assessment of the Regional Drinking Water Company (PDAM) "Delta Tirta" Waru II Branch Sidoarjo Regency shows that the quality of the service of PDAM Waru II Branch Sidoarjo Regency reaches (4.01). Based on the results of calculations using the servqual method on 5 indicators of public service quality assessment: 1. Tangible has an average score of performance (3.78), 2. Reliability has an average score of performance (4.29), 3. Responsiveness has an average score performance average (3.69), 4. Assurance has an average performance score (4.26), and Empathy has an average performance score (4.22).